Performance Sensitivity of Executive Pay: The Role of Foreign Investors and Affiliated Directors in Japan - COLPAN, Asli M. (Institutional Knowledge at Singapore Management University, 2012)
This study investigates the effects of corporate governance factors on the firm performance and executive compensation linkage. Specifically, we examine how domestic corporate-appointed directors, bank-appointed directors and foreign ownership moderate the relationship between firm profitability, sales growth, and executive bonus pay in Japanese firms. Using a sample of the largest Japanese manufacturing companies from 1997 to 2007, we find that corporate-appointed directors positively moderate the relationship between firm growth and bonus pay, while foreign shareholders exhibit a positive moderating effect on the relationship between firm profitability and bonus pay. Bank-appointed directors are straddled between their profitability orientation and relational role: They link firm profitability and bonus pay, but also show positive influence on the firm growth and bonus pay relationship. Our findings offer insights to stakeholders to pay attention to ownership structure and board composition in acknowledging the varied financial motivation of executives to pursue growth and/or profitability.